A case study for rebar-reinforced shotcrete arches and void filling at the Grasberg Block Cave mine, Indonesia - Setiawan, A.; Cahyono, B.; Kriska, B.; Ginting, R.; Napitupulu, D. (Ground Support 2023: Proceedings of the 10th International Conference on Ground Support in Mining, 2023)
The Grasberg block cave mine was developed below the Grasberg open pit at PT Freeport Indonesia as part of the transition to underground mining. The initial access drifts were developed in 2004 and production started in 2018, with a projected peak production of 160,000 t per day. During the development stage of the Drainage Drift 4, it became clear that the geological conditions would be a key parameter in the stability and sequence of these excavations. Where the lithological contact between the Faumai limestone and heavy sulphide zone (HSZ) coincided with the mid Grasberg fault zone, very poor ground conditions and short excavation stand up times lead to tunnel collapses and severe overbreak. Furthermore, a void was created due to the mucking operations. Void assessment using scan and drilling data was conducted to determine the void boundaries that would be concrete filled. A combination of spiling bars, rebar reinforced shotcrete arches (RRSA), and cable bolts were installed during the excavation process in these poor ground conditions. These ground support types and combinations, particularly the RRSA were designed to provide long-term stability for the excavations. This paper discusses the development of the various ground support strategies with reference to the RRSA including ground support capacity analysis.